2010
DOI: 10.3928/00989134-20100330-06
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Statewide Medication Technician Pilot Program in Nursing Homes

Abstract: In times of fiscal constraints, nursing homes are seeking to maximize use of licensed staff through delegation of low-risk tasks to unlicensed personnel. Between 2004 and 2008, the Arizona State Board of Nursing developed and conducted a pilot program to determine the impact on patient health and safety of licensed nurses delegating medication administration to trained certified nursing assistants. There were no differences in patterns of medication errors before and after the introduction of medication techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This holistic approach at the heart of nursing may be at threat from a rationing or task-orientated approach which has been associated with increased incidents of missed care, lower satisfaction, and poor staff retention ( Mandal et al., 2020 ). The evidence reported in this review from four studies ( Kapborg and Svensson, 1999 ; Young et al., 2008 ; Randolph and Scott-Cawiezell, 2010 ; Hughes et al., 2006 ) presents mixed findings on medication errors related to non-registered support workers and a lack of comparison of error rates between registered nurses and non-registered support workers. Findings reiterate the importance of creating a patient safety culture that encourages reporting and learning from errors as this has been linked to improved patient outcomes ( Bonner et al., 2009 , Thomas et al., 2012 2).…”
Section: Discussionmentioning
confidence: 83%
“…This holistic approach at the heart of nursing may be at threat from a rationing or task-orientated approach which has been associated with increased incidents of missed care, lower satisfaction, and poor staff retention ( Mandal et al., 2020 ). The evidence reported in this review from four studies ( Kapborg and Svensson, 1999 ; Young et al., 2008 ; Randolph and Scott-Cawiezell, 2010 ; Hughes et al., 2006 ) presents mixed findings on medication errors related to non-registered support workers and a lack of comparison of error rates between registered nurses and non-registered support workers. Findings reiterate the importance of creating a patient safety culture that encourages reporting and learning from errors as this has been linked to improved patient outcomes ( Bonner et al., 2009 , Thomas et al., 2012 2).…”
Section: Discussionmentioning
confidence: 83%
“…Our study found that delegating medicines support to CCAs did not increase the rate of medication incidents. Several studies have reported similar findings [ 31 , 34 , 35 ], while others have reported medication incidents associated with use of care workers [ 9 , 20 , 36 , 37 ] or have been inconclusive [ 8 , 14 , 15 ]. Consistent with our findings, previous studies have reported that using care workers for medicines support could provide opportunities for cost-saving [ 8 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 92%
“…Several studies investigated associations between care workers’ involvement in medicine support and a range of outcomes in residential care and hospital settings [ 14 , 31 35 ]. They reported evidence that care workers’ involvement in medicine support could lead to improved job satisfaction for both nurses and care workers, as well as improved people’s satisfaction with care, and improved quality of care by reducing workload pressure on nurses, enabled nurses to spend more time undertaking complex nursing activities [ 14 , 20 , 31 , 33 , 34 ]. Similarly, our study found that an expanded CCA role in medicines support resulted in improved job satisfaction for CCAs, that nurses and clients were generally comfortable with the role, and that it sometimes freed up nurses to spend time on more complex nursing tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2007). Most recently, Randolph & Scott‐Cawiezell reported no differences in patterns of medication errors in nursing homes before and after the introduction of medication technicians (Randolph & Scott‐Cawiezell, 2010).…”
Section: Resultsmentioning
confidence: 99%